Northwest History. Alaska, Glaciers. United States. (1937)
Glacier On Go. Glacier On Go FAIRBANKS, Alalka, March 24. (JP)—The meandering Black Rapids glacier, which threatens to wipe out Revell's roadhouse and block interior Alaska's only automobile artery to the sea, is continuing its forward movement but with a . slower pace, H. E. Revell, owner of the roadhouse, said today. The glacier, which had receded for years until earthquakes sent it forward about December 3, has moved about six miles in 16 weeks, and now is only a mile and a quarter from the roadhouse, 130 miles southeast of here on the Richardson highway and the Big Delta river.